2021
DOI: 10.3389/fimmu.2021.635767
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapeutic Strategies to Restore Regulatory T Cell Control of Islet Autoimmunity in Type 1 Diabetes

Abstract: Despite many decades of investigation uncovering the autoimmune mechanisms underlying Type 1 Diabetes (T1D), translating these findings into effective therapeutics has proven extremely challenging. T1D is caused by autoreactive T cells that become inappropriately activated and kill the β cells in the pancreas, resulting in insulin insufficiency and hyperglycemia. A large body of evidence supports the idea that the unchecked activation and expansion of autoreactive T cells in T1D is due to defects in immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…DKD, also known as diabetic nephropathy [ 9 , 10 , 11 , 12 , 13 ], is a common complication of diabetic mellitus, including both type 1 and type 2 diabetes. While type 1 diabetes is caused by lack of insulin due to pancreatic β cell destruction [ 14 , 15 , 16 ], type 2 diabetes could be caused by insulin resistance or insulin deficiency [ 17 , 18 , 19 , 20 , 21 , 22 ]. The hallmark of diabetes is a persistent high blood glucose content (hyperglycemia) that can damage a variety of tissues and cells [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…DKD, also known as diabetic nephropathy [ 9 , 10 , 11 , 12 , 13 ], is a common complication of diabetic mellitus, including both type 1 and type 2 diabetes. While type 1 diabetes is caused by lack of insulin due to pancreatic β cell destruction [ 14 , 15 , 16 ], type 2 diabetes could be caused by insulin resistance or insulin deficiency [ 17 , 18 , 19 , 20 , 21 , 22 ]. The hallmark of diabetes is a persistent high blood glucose content (hyperglycemia) that can damage a variety of tissues and cells [ 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging evidence on the role of EGR2 in the natural history of diabetes, through the development of insulin resistance which is increasingly observed in people with T1D [37] to the progression of complications [38, 39]. Recent studies which revealed crucial roles of EGR2 in the induction of T cell anergy and suppression of activities mediated by LAG3+ regulatory T cells (Tregs) are intriguing [40], given that Tregs are strongly implicated in T1D etiopathogenesis [41] and extensively investigated as therapeutic targets to ameliorate islet autoimmunity of T1D [42].…”
Section: Discussionmentioning
confidence: 99%
“…given that Tregs are strongly implicated in T1D etiopathogenesis [41] and extensively investigated as therapeutic targets to ameliorate islet autoimmunity of T1D [42].…”
Section: Marker Genes Of Incident T1d In Pbmc Of Children: Biological...mentioning
confidence: 99%
“…Both subsets of FOXP3-positive Tregs can inhibit and downregulate effector T cell proliferation and cytokine production and play a critical role in preventing autoimmunity [ 183 , 184 ]. Repairing the defects in Treg in order to restore the defects in immune system regulation is a potential strategy for disease treatment [ 185 ].…”
Section: Factors Affecting the Progression Of Autoimmunitymentioning
confidence: 99%